708 Examining the Management of Acute Lower GI Bleeds in Order to Improve Policies and Reflect Safe and Updated Guidance. (4th May 2021) - Han, L; White, H; Bosch, K; Nair, M
Abstract: Introduction: Acute lower gastrointestinal bleeding (LGIB) tends to occur in elderly patients with complex comorbidities. At North Middlesex University Hospital (NMUH), LGIB patients are primarily managed by the surgical department. We amended local policies by integrating aspects of new guidelines published by the British Society of Gastroenterology (BSG). Method: Handover documentation between November 2019 and January 2020 established patients admitted with LGIB (n = 45). Further data regarding the management of these patients was collated from clinical software and compared to standards set from BSG guidelines. Results: We found NMUH to be efficient in ruling out upper GI bleeds via 24-hour OGDs and had low surgical intervention rates (0.02%). 40% of patients were transfused with an admission haemoglobin above suggested NICE thresholds, accounting for cardiovascular comorbidities. 56% of patients were discharged without a documented anticoagulation plan. Over 50% of patients did not have BSG recommended inpatient investigations. Conclusions: Updated Trust guidelines aim to uphold areas that NMUH were shown to excel in, while reiterating NICE transfusion thresholds and include guidance regarding anticoagulant and antiplatelet medications. The Oakland score and shock index have been integrated into local protocols and will aid clinicians in making safe decisions in the management of LGIB patients.